Best Practices for Planning Events Encouraging Human–Animal Interactions. (3rd April 2014) - Erdozain, G.; KuKanich, K.; Chapman, B.; Powell, D.
Summary Educational events encouraging human–animal interaction include the risk of zoonotic disease transmission. It is estimated that 14% of all disease in the USA caused by Campylobacter spp., Cryptosporidium spp., Shiga toxin‐producing Escherichia coli (STEC) O157, non‐O157 STECs, Listeria monocytogenes, non‐typhoidal Salmonella enterica and Yersinia enterocolitica were attributable to animal contact. This article reviews best practices for organizing events where human–animal interactions are encouraged, with the objective of lowering the risk of zoonotic disease transmission.